STRATEGI PENINGKATAN KUALITAS PELAYANAN PENDIDIKAN PADA PERGURUAN TINGGI - Wahyu Ismail Kurnia; Radeng Hendang; Atina Buton (Journal of Industrial Engineering Management, 2019)
Service quality is the totality of the characteristics of goods and services used to meet customer needs, the visible and the invisible. The quality of education services in the industrial engineering department of Iqra Buru Namlea university is still very decent, it needs to be improved. The purpose of this study is to study the quality needs of education and develop strategies to improve the quality of educational services in the Department of Industrial Engineering, Iqra Buru Namlea University. This study uses Servqual (quality of service) and QFD (Quality Function Deployment) methods in planning and developing strategies to improve the quality of education services. Based on the Service Quality method, several service attributes were obtained that did not meet the students' expectations, which were then processed using the Qualituy Function Deployment method. In this process, the improvement process in the education sector resulted in management needs to be done, one of which is, lecturers make a schedule of meetings with students for final assignment and guardianship guidance and lecturers improve work coordination so that students' expectations can support and the academic guidance process can be carried out properly